2008
DOI: 10.1029/2008ja013062
|View full text |Cite
|
Sign up to set email alerts
|

Modeling spectra of the north and south Jovian X‐ray auroras

Abstract: [1] Spectra of Jovian X-ray auroras observed from the North and South poles with the Chandra X-ray telescope are analyzed and compared with predicted spectra of the charge-exchange mechanism. To determine the theoretical spectra of Jovian X-ray auroras, we model numerically the collisionally induced evolution of energy and charge distributions of O q+ and S q+ ions, precipitating into the Jovian atmosphere. Monte Carlo simulations of the energy and charge relaxation of the precipitating ions are carried out wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
66
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(71 citation statements)
references
References 29 publications
(147 reference statements)
5
66
0
Order By: Relevance
“…Regarding the auroral soft X‐ray spectra, a series of observations and analyses have been carried out to infer the compositions of the precipitating ion fluxes [e.g., Elsner et al , 2005; Branduardi‐Raymont et al , 2004, 2007a, 2007b], while theoretical modeling based on simulations of the emission following charge exchange between heavy ions and molecular hydrogen has been developed to constrain the ion energies and abundances at the top of the Jovian atmosphere [ Metzger et al , 1983; Horanyi et al , 1988; Waite et al , 1994; Cravens et al , 1995; Kharchenko et al , 1998; Liu and Schultz , 1999; Kharchenko et al , 2006, 2008]. It has been established that highly charged oxygen and sulfur ions with MeV/u initial energies can account for the observed line emissions in the Chandra and XMM‐Newton spectra.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the auroral soft X‐ray spectra, a series of observations and analyses have been carried out to infer the compositions of the precipitating ion fluxes [e.g., Elsner et al , 2005; Branduardi‐Raymont et al , 2004, 2007a, 2007b], while theoretical modeling based on simulations of the emission following charge exchange between heavy ions and molecular hydrogen has been developed to constrain the ion energies and abundances at the top of the Jovian atmosphere [ Metzger et al , 1983; Horanyi et al , 1988; Waite et al , 1994; Cravens et al , 1995; Kharchenko et al , 1998; Liu and Schultz , 1999; Kharchenko et al , 2006, 2008]. It has been established that highly charged oxygen and sulfur ions with MeV/u initial energies can account for the observed line emissions in the Chandra and XMM‐Newton spectra.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Bunce et al [2004] suggested that pulsed magnetic reconnection on the dayside Jovian magnetopause produces bipolar field‐aligned currents that would, for certain solar wind conditions, accelerate magnetospheric ions. To distinguish between these two ion sources and to seek better constraints on other characteristics such as the ion acceleration mechanism, we have improved and extended our recent spectral model [ Kharchenko et al , 2008] and added the contribution of carbon ions, the most abundant heavy element in the solar wind after oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…Kharchenko et al 1998Kharchenko et al , 2008Hui et al 2009Hui et al , 2010a. Unlike for CSDA, no assumption is made on the charge state fraction, the particle charge state being recorded after each collision.…”
Section: Energetic Ionsmentioning
confidence: 99%
“…Descriptions of a theoretical model of charge-exchangeinduced X-rays in the Solar System and calculated emission spectra have been previously published (Kharchenko et al 1998(Kharchenko et al , 2008Kharchenko & Dalgarno 2000;Koutroumpa et al 2006;Bhardwaj et al 2007). We consider collisions between heavy SW ions and hydrogen gas, X Q+ + H → X * (Q−1)+ + H + , taking into account that H is a predominant component of interstellar gas.…”
Section: Polarization Of the Emissions Induced In Charge-exchange Colmentioning
confidence: 99%